Neurophysiological Correlates of Configural Face Processing in Schizotypy - Batty, Rachel A.; Francis, Andrew J. P.; Innes-Brown, Hamish; Joshua, Nicole R.; Rossell, Susan L. (Frontiers in Psychiatry, 2014)
Background: Face processing impairment in schizophrenia appears to be underpinned by poor configural (as opposed to feature-based) processing, however few studies have sought to characterize this impairment electrophysiologically. Given the sensitivity of event-related potentials (ERPs) to antipsychotic medications, and the potential for neurophysiological abnormalities to serve as vulnerability markers for schizophrenia, a handful of studies have investigated early visual P100 and face-selective N170 in “at risk” populations. However, this is the first known neurophysiological investigation of configural face processing in a non-clinical schizotypal sample. Methods: Using stimuli designed to engage configural processing in face perception (upright and inverted Mooney and photographic faces), P100 and N170 components were recorded in healthy individuals characterized by high (N=14) and low (N=14) schizotypal traits according to the Oxford-Liverpool Inventory of Feelings and Experiences (O-LIFE). Results: High schizotypes showed significantly reduced N170 amplitudes to inverted photographic faces. Typical N170 latency and amplitude inversion effects (delayed and enhanced N170 to inverted relative to upright photographic faces, and enhanced amplitude to upright versus inverted Mooney faces), were demonstrated by low, but not high, schizotypes. No group differences were shown for P100 analyses. Conclusions: The findings suggest that neurophysiological deficits in processing facial configurations (N170) are apparent in schizotypy, while the early sensory processing (P100) of faces appears intact. This work adds to the mounting evidence for analogous neural processing anomalies at the healthy end of the psychosis continuum.